2018
DOI: 10.2471/blt.17.192658
|View full text |Cite
|
Sign up to set email alerts
|

Untreated depression and tuberculosis treatment outcomes, quality of life and disability, Ethiopia

Abstract: ObjectiveTo investigate the association between comorbid depression and tuberculosis treatment outcomes, quality of life and disability in Ethiopia.MethodsThe study involved 648 consecutive adults treated for tuberculosis at 14 primary health-care facilities. All were assessed at treatment initiation (i.e. baseline) and after 2 and 6 months. We defined probable depression as a score of 10 or above on the nine-item Patient Health Questionnaire. Data on treatment default, failure and success and on death were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 40 publications
2
80
2
6
Order By: Relevance
“…Analysis of TB treatment outcomes revealed a higher risk of negative outcomes, lower success rate, and worse adherence to treatment among patients who presented DS. One study reported an adjusted hazard ratio of 3.46 for treatment default or death in patients with symptoms suggestive of a major depressive episode (MDE) at baseline visit [3], while another also found an increased risk for loss to follow-up and death (RR = 9.09 and 2.99, respectively) in persons with an MDE score suggestive of depression at baseline [20]. In the largest study measuring depression, the authors showed that in comparison with individuals with low depression scores, those with high scores had a greater chance of poor medication adherence (OR = 3.67) [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of TB treatment outcomes revealed a higher risk of negative outcomes, lower success rate, and worse adherence to treatment among patients who presented DS. One study reported an adjusted hazard ratio of 3.46 for treatment default or death in patients with symptoms suggestive of a major depressive episode (MDE) at baseline visit [3], while another also found an increased risk for loss to follow-up and death (RR = 9.09 and 2.99, respectively) in persons with an MDE score suggestive of depression at baseline [20]. In the largest study measuring depression, the authors showed that in comparison with individuals with low depression scores, those with high scores had a greater chance of poor medication adherence (OR = 3.67) [18].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, within each measurement of exposure, different psychometric instruments and cut-off scores were employed. In the case of studies that measured DS, there was notable variability between the scales used: a brief 5-item and the full 20-item version of the CES-D scale, and the PHQ-9 scale [3,18,20]. Others reported results using the exposure as a numeric variable alone [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Post-traumatic disorder among TB patients was 29.6% in South Africa (Peltzer et al, 2013). Mental illnesses are also a cause of poor quality of life, TB treatment interruption, and poor treatment outcomes (Ambaw et al, 2018;Pachi et al, 2013;Sikjaer et al, 2018;Theron et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This co-morbidity depression is related to the nature of the illness, biological factors, social (stigma, poverty), and behavioral factors (substance use) (5)(6)(7)(8)(9). In Ethiopia, epidemiological evidence showed that the prevalence of depression among individual with TB ranged from 18% to 67% (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). This co-morbid depression was associated with poor treatment adherence, MRD-TB, suicide, substance use and poor quality of life (9,10,22).…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, epidemiological evidence showed that the prevalence of depression among individual with TB ranged from 18% to 67% (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). This co-morbid depression was associated with poor treatment adherence, MRD-TB, suicide, substance use and poor quality of life (9,10,22). Although, these individual studies are important, the variation in reported prevalence of depression and its determinant factors need comprehensive up to date information.…”
Section: Introductionmentioning
confidence: 99%